2013
DOI: 10.1128/genomea.00770-13
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Lactobacillus fermentum Strain MTCC 8711, a Probiotic Bacterium Isolated from Yogurt

Abstract: Lactobacillus fermentum strain MTCC 8711 is a lactic acid bacterium isolated from yogurt. Here, we describe the draft genome sequence and annotation of this strain. The 2,566,297-bp-long genome consisted of a single chromosome and seven plasmids. The genome contains 2,609 protein-coding and 74 RNA genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 3 publications
(3 reference statements)
1
10
0
2
Order By: Relevance
“…Versatile vectors have been developed for high-level, inducible gene expression in Lactobacillus sakei and Lactobacillus plantarum (Sorvig et al, 2005 ). In the GenBank database, 166 plasmids were found in Lactobacillus , and notably, multiple (five to ten) plasmids were found in individual strains, such as Lactobacillus fermentum MTCC 8711 (Jayashree et al, 2013 ), Lactobacillus plantarum 16 (Crowley et al, 2013 ), and Lactobacillus reuteri I5007 (Hou et al, 2014 ). Fukao et al reported that one of the LAB, L. brevis KB290, has nine plasmids with RepABC systems (Fukao et al, 2013 ).…”
Section: Plasmids In Firmicutesmentioning
confidence: 99%
“…Versatile vectors have been developed for high-level, inducible gene expression in Lactobacillus sakei and Lactobacillus plantarum (Sorvig et al, 2005 ). In the GenBank database, 166 plasmids were found in Lactobacillus , and notably, multiple (five to ten) plasmids were found in individual strains, such as Lactobacillus fermentum MTCC 8711 (Jayashree et al, 2013 ), Lactobacillus plantarum 16 (Crowley et al, 2013 ), and Lactobacillus reuteri I5007 (Hou et al, 2014 ). Fukao et al reported that one of the LAB, L. brevis KB290, has nine plasmids with RepABC systems (Fukao et al, 2013 ).…”
Section: Plasmids In Firmicutesmentioning
confidence: 99%
“… 4 In this regard, many research have been conducted on the isolation and evaluation of probiotic potential bacteria and in turn establishment of a biobank to save them from destruction, for future applications in medicine and food industry. Today, the probiotic human-friendly bacteria are isolated from foods, cheese, 5 yogurt, 6 , 7 fermented olives, 8 and wine, 9 as well as human himself, human milk, 10 , 11 infant feces, 12 women vagina, 13 etc. According to WHO guidelines for evaluation of probiotics, putative strains should be screened for resistance to gastric acidity and bile salts, antimicrobial compound production and safety properties such as antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…L. fermentum is a Gram-positive, heterofermentative lactic acid bacterium which is wildly used in the production of fermented food 53 . It was reported that the pH of L. fermentum culture dramatically affects the product of fermentation 54 .…”
Section: Resultsmentioning
confidence: 99%